Improving block management in 3D NAND flash SSDs with sub-block first write sequencing - Buddhanoy, Matchima, author; Khan, Kamil, author; Milenkovic, Aleksandar, author; Pasricha, Sudeep, author; Ray, Biswajit, author; ACM, publisher (Colorado State University. Libraries, 2024)
Continual vertical scaling in 3D NAND flash solid-state drives (SSDs) results in larger memory blocks, causing performance degradation due to big-block management issues. Pages within a 3D NAND flash block are traditionally written using layer first write sequencing. This paper introduces and explores the benefits of an alternative sub-block first write sequence. This method when coupled with sub-block erase operations promises to alleviate the big-block problem. Our evaluation on a commercial 32-layer 3D NAND flash SSD chip shows that though the proposed method increases the raw bit error rate (RBER), it remains below the threshold that can be corrected by error correction codes (ECCs). Simulation analysis further shows that our proposed method reduces garbage collection overhead, resulting in 36.0% lower response time and 9.6% reduction in additional writes due to garbage collection compared to traditional 3D NAND flash SSDs.
Keywords: flash memories; sub-block write; SSD storage; garbage collection; write amplification